Surgical Technique and Case Series of Total Hip Arthroplasty with the Hueter Anterior Approach for Crowe Type-IV Dysplasia. (4th November 2020) - Viamont-Guerra, Maria-Roxana; Saffarini, Mo; Laude, Frederic
Abstract : Background: Total hip arthroplasty (THA) is being increasingly performed via the Hueter anterior approach (HAA), which has proven benefits with nondysplastic hips; however, little has been published on its outcomes with dysplastic hips, where it can provide better acetabular exposure. We describe our technique for THA via the HAA in hips with Crowe type-IV developmental dysplasia and report the mid-term outcomes of cases that were performed over 5 consecutive years. Methods: We retrospectively evaluated a continuous series of 8 hips (6 patients) with Crowe type-IV dysplasia; the patient ages ranged from 44 ± 20 years (range, 17 to 65 years) at the index THA. All of the patients received uncemented implants via the HAA on a traction table to restore the hip center of rotation to the true acetabulum. Femoral head autografts (FHAs) were used to increase acetabular coverage in 6 hips, and subtrochanteric shortening osteotomies (SSOs) were performed in 5 hips. Patients were assessed clinically and radiographically at a minimum follow-up of 2 years. Results: There were no revisions, deaths, dislocations, or infections. Two hips (25%) had intraoperative complications, and 1 hip (13%) had a postoperative complication that required reoperation without implant removal. All of the hips were assessed clinically and radiographically at 4 ± 1 years (range, 2 to 6 years). The modified Harris hip score (mHHS) improved from 33 ± 7 to 90 ± 7, and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) improved from 53 ± 14 to 89 ± 6; the postoperative leg-length discrepancy was 3.2 mm (range, −10 to 20 mm). None of the hips had osteolysis or radiolucent lines of >2 mm. Conclusions: THA via the HAA on a traction table for hips with Crowe type-IV dysplasia yielded satisfactory mid-term outcomes. Both FHA and SSO can be adequately performed via the HAA to help restore the hip center of rotation to the true acetabulum. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.